Determinanty kształtowania jakości usługi podczas współprodukcji - Wiesław Urban (Polityki Europejskie, Finanse i Marketing)
This article aims to recognize and prioritize factors that influence the setting of service guidelines during its co-production. Critical Incident Technique is employed. There were 171 descriptions of incidents collected from customer service staff. The research shows that in establishing the guidelines for services the most important is the staff’s knowledge and communication skills. Fundamental problem with the service co-production lies in the fact that customers are not able to determine their own expectations.